2022
DOI: 10.3390/ijerph19074354
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF Mass Spectrometry Analysis and Human Post-Mortem Microbial Community: A Pilot Study

Abstract: Introduction: The human post-mortem microbiome (HPM) plays a major role in the decomposition process. Successional changes in post-mortem bacterial communities have been recently demonstrated using high throughput metagenomic sequencing techniques, showing great potential as a post-mortem interval (PMI) predictor. The aim of this study is to verify the application of the mass spectrometry technique, better known as MALDI-TOF MS (matrix-assisted laser desorption/ionization time-of-flight mass spectrometry), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Different studies showed an increase in bacterial richness and a decrease in diversity from the early to late decomposition stages (Table 1) [9,70]. These studies have also consistently demonstrated an increase in Pseudomonadota and a decrease in Actinomycetota and Bacteroidota, with particular relevance in the rectum [71,72]. Additionally, another study has reported a negative linear relationship between the overall phylum and family taxa with PMI.…”
Section: Body Decomposition and Microbial Succession After Deathmentioning
confidence: 82%
See 1 more Smart Citation
“…Different studies showed an increase in bacterial richness and a decrease in diversity from the early to late decomposition stages (Table 1) [9,70]. These studies have also consistently demonstrated an increase in Pseudomonadota and a decrease in Actinomycetota and Bacteroidota, with particular relevance in the rectum [71,72]. Additionally, another study has reported a negative linear relationship between the overall phylum and family taxa with PMI.…”
Section: Body Decomposition and Microbial Succession After Deathmentioning
confidence: 82%
“…Other approaches involving transcriptomics and proteomics, which provide functional community information and/or a global snapshot of the physiological and biochemical state of a sample, can be highly valuable (e.g., when DNA is absent or degraded as in hair or bone samples) and are increasingly explored [152,153]. Also, flow cytometry (evaluating DNA degradation) and MALDITOF-MS (Matrix-assisted laser desorption/ionization timeof-flight mass spectrometry) or MALDI-IMS (Matrix-assisted laser desorption/ionization imaging mass spectrometry), respectively able to accurately identify bacteria at the species level and profiling the proteins and peptides in tissue sections, have been explored as promising tools for PMI calculation [71,154,155].…”
Section: Culture-independent Methodsmentioning
confidence: 99%
“…The most abundant taxa of microbial communities according to the organ examined are Firmicutes in the brain, heart and spleen [12,24,30]; Firmicutes and Proteobacteria in the liver [12,13,30]; Bacteroidetes, Firmicutes and Pro-teobacteria in the oral cavity [31]; Acidobacteria, Actinobacteria, Bacteroidetes, Chloroflexi, Firmicutes and Proteobacteria in the bones [32]. According to another study, the predominant phyla in the post-mortem microbiota are Firmicutes and Proteobacteria [33].…”
Section: Patterns Of Microbial Dynamics After Deathmentioning
confidence: 95%